Experimental Study on Strength and Buoyancy of Lightweight Concrete Containing Sustainable Materials - Nik Mohd Zaid, Nik Mohamad Zulfarisham; Mohamed, Maziana (Research and Innovation in Technical and Vocational Education and Training, 2022)
To meet current demand, the building industry is focusing on sustainable alternative materials to conventional concrete. Lightweight concrete is becoming increasingly popular as a viable solution for meeting structural, economic, and environmental requirements. The study was aimed at producing pontoons measuring 500mm x 500mm x 100mm using sustainable materials such as LECA Ball and PVC pipes that are capable of floating on water and to identify the appropriate mixing ratio of concrete materials to produce lightweight concrete that has high compressive strength and buoyancy. A total of 36 samples for the cube test and 6 samples for the pontoon were used as test material to meet the objectives of this study. Concrete cube specimens were tested after the curing period on the 7th and 28th days. While the pontoon concrete was tested on the 28th day for buoyancy. The results from the test that have been conducted show that the concrete mix that produces the highest average compressive strength is mix proportion 1: 1: 2, which is 13.997 N/mm2, while for the buoyancy test, the mix proportion that can accommodate the highest maximum load is 1.5: 1: 2, i.e., 6.788 kg.